Kajian Hukum Tentang Pernikahan di Usia Dini Studi Kasus Kelurahan Batang Terap (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Early marriage is a marriage between a couple of teenagers under 18 years old or still studying at high school level. Marriage is a ceremony to unite the marriage bond between a woman and a man legally in the eyes of religion and law. Early marriage has a high risk on the reproductive health of young women. The impact of early marriage on young women results in reproductive health problems for women, physical, psychological and psychosocial health. Apart from that, mental readiness at adolescence to face something new as a mother and wife requires mental readiness and mature thinking to make the decision to marry as a teenage girl, so the government provides new regulations for a minimum marriage age of 19 years. Young marriages are marriages carried out by teenagers under the age of 20 who are not yet ready to get married. Indonesia is ranked 37th in the world and 2nd in ASEAN as a country with a high rate of young marriage. The results of this research show that mothers who marry at a young age have the intention to continue the tradition of marrying at a young age which can be described by background factors and local habits/customs theory. Therefore, cooperation is needed including the government, community leaders and related institutions (KUA and Community Health Centers) to reduce and prevent the incidence of marriage at a young age.